Deep-lacustrine sandy debrites and turbidites in the lower Triassic Yanchang Formation, southeast Ordos Basin, central China: Facies distribution and reservoir quality. (November 2016) - Xu, Qinghai; Shi, Wanzhong; Xie, Xiangyang; Manger, Walter; McGuire, Preston; Zhang, Xiaoming; Wang, Ren; Xu, Zhuang
Abstract: The deep lacustrine gravity-flow deposits are widely developed in the lower Triassic Yanchang Formation, southeast Ordos Basin, central China. Three lithofacies include massive fine-grained sandstone, banded sandstone, and massive oil shale and mudstone. The massive fine-grained sandstones have sharp upper contacts, mud clasts, boxed-shaped Gamma Ray (GR) log, but no grading and Bouma sequences. In contrast, the banded sandstones display different bedding characteristics, gradational upper contacts, and fine-upward. The massive, fine-grained sandstones recognized in this study are sandy debrites deposited by sandy debris flows, while the banded sandstones are turbidites deposited by turbidity currents not bottom currents. The sediment source for these deep gravity-flow sediments is a sand-rich delta system prograding at the basin margin. Fabric of the debrites in the sandy debris fields indicates initial formation from slope failure caused by the tectonic movement. As the sandy debris flows became diluted by water and clay, they became turbidity currents. The deep lacustrine depositional model is different from the traditional marine fan or turbidite fan models. There are no channels or wide lobate sand bodies. In the lower Triassic Yanchang Formation, layers within the sandy debrites have higher porosity (8–14%) and permeability (0.1–4 mD) than the turbidites with lower porosity (3–8%) and permeability (0.04–1 mD). Consequently, only the sandy debrites constitute potential petroleum reservoir intervals. Results of this study may serve as a model for hydrocarbon exploration and production for deep-lacustrine reservoirs from gravity-flow systems in similar lacustrine depositional environments. Highlights: The ancient deep lacustrine gravity-flow sediments are mainly composed of sandy debrites with associated turbidites. Discussed the depositional model, including the trigger mechanisms, flows transformation. Summarize the differences between the deep lacustrine turbidites and deep marine turbidites. Sandy debrites have higher reservoir quality than those beds deposited as turbidites.